Confronting new challenges : 1995 : report on the work of the Organisation from the Forty-Ninth to Fiftieth Session of the General Assembly - Boutros-Ghali, Boutros (UN New YorkUS, 1995)
Focuses on the efforts of the Organization to respond effectively to the multitude of new demands and problems resulting from the dramatic changes engendered by the end of the cold war.